2008
DOI: 10.1287/mksc.1070.0353
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Local Environments with Global Strategies: A Contingency Model of Multinational Subsidiary Performance

Abstract: Multinational corporations (MNCs) often pursue global strategies that emphasize efficiency, flexibility, and learning, but globally developed strategies often clash with the environmental idiosyncrasies of MNC country subsidiary markets in which the strategy is actually implemented. Extant research pays little attention to the contingent efficacy of such global strategies from the perspective of MNC country subsidiary markets. We adopt the strategy-environment alignment principle and study how host country tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 58 publications
(48 reference statements)
0
32
0
Order By: Relevance
“…The methods are attributed to Croon (2002) and to Skrondal and Laake (2001). Although these methods were proposed nearly a decade ago, our review found only two instances of their application in published empirical research (Grewal, Chandrashekaran, & Dwyer, 2008;Grewal & Slotegraaf, 2007). As the new methods were introduced in rather technical literature, an understanding of the process of implementation may be inaccessible to a non-mathematical audience.…”
Section: Introductionmentioning
confidence: 99%
“…The methods are attributed to Croon (2002) and to Skrondal and Laake (2001). Although these methods were proposed nearly a decade ago, our review found only two instances of their application in published empirical research (Grewal, Chandrashekaran, & Dwyer, 2008;Grewal & Slotegraaf, 2007). As the new methods were introduced in rather technical literature, an understanding of the process of implementation may be inaccessible to a non-mathematical audience.…”
Section: Introductionmentioning
confidence: 99%
“…to which the MNC emphasized a particular global strategy, we adopted measures developed by Grewal, Chandrashekaran, and Dwyer (2008). These measures assess the extent to which the MNC emphasizes a specific strategy from subsidiary managers' perspective.…”
Section: Methodsmentioning
confidence: 99%
“…Drawing on extant research on the mean-variance modeling of consumer judgments (Chandrashekaran et al, 2007;Grewal, Chandrashekaran, & Dwyer, 2008) and satisfaction (Chandrashekaran, Rotte, & Grewal, 2005), let SAT i denote the stated satisfaction of the ith consumer and recognize that SAT i is a realization from a distribution of possible satisfaction. While satisfaction magnitude is captured by the central tendency of that distribution, lack of satisfaction certainty is manifested in greater variance of that distribution.…”
Section: A Framework Of the Analysismentioning
confidence: 99%
“…This research is also motivated by marketing modeling literature that decomposes attitude into attitude magnitude and attitude uncertainty (Grewal, Chandrashekaran, & Dwyer, 2008;Chandrashekaran, McNeilly, Russ, & Marinova, 2000;Chandrashekaran, Rotte, & Grewal, 2005;Chandrashekaran et al, 2007;Rotte et al, 2006Rotte et al, , 2009. Captured by the Judgment Uncertainty and Magnitude Parameters (JUMP) model (see Chandrashekaran et al, 2000Chandrashekaran et al, , 2005, this twodimensional view of attitude resonates with the vast literature on attitude uncertainty (Gross, Holtz, & Miller, 1995).…”
mentioning
confidence: 99%